(untitled) (Medicine Today, 2025)
Introduction: Asymptomatic bacteriuria (ASB), or asymptomatic urinary infection, is isolation of a specified quantitative count of bacteria in an appropriately collected urine specimen obtained from a person without symptoms or signs referable to urinary infection. Patients with diabetes mellitus (DM) have a high frequency of ASB and urinary tract infections (UTIs). High glucose concentration in the urine of DM patients may favour the growth of uropathogens. Early detection, strict glycemic control and proper treatment prevent the burden of asymptomaticbacteriuria. Objectives: To observe the frequency of asymptomatic bacteriuria and common isolates among diabetic patients. Materials & Methods: This cross-sectional study was conducted amongst diabetic patients from March 2016 to December 2016. Sample was selected by purposive sampling technique. Patients with DM were selected for study. Sample size was 72. Mid-stream urine samples collected into sterile container for urinalysis. Cultures with colony counts ≥ 105cfu/ ml were considered as significant bacteriuria. Detail demographic data were collected from the informant and recorded in structured case report form. Clinical examination and relevant investigation were done meticulously. Result: Mean age of patients was 56.04±18.08 yrs. Female patients were predominant, out of 72 cases 32(44%) were male and 40(56%) were female. Present study showed that ASB was present in 57(79.16%) patients and E. coli was the most common pathogen. Other isolates included Klebsiella pneumoniae 11(19.29%), Proteus sp. 6(10.52%) and Enterobacter sp. 5(8.77%). Conclusion: Asymptomatic bacteriuria is common in DM patients. The occurrence of ASB in the older population and females was significant in this study. ASB may lead to albuminuria and urinary tract infection, and may warrant treatment in diabetics. So it is recommend screening for detection and treatment of ASB in diabetic patients should be routinely. Medicine Today 2025, Vol.37 (2): 179-182